Analysis of the Effect of Competency and Transformational Leadership on Employee Performance with Quality of Work Life as a Mediating Variable - Diana Oktafarina; Muchlis Mas'ud (Optima Science, 2024)
The research aims to determine the effect of competency and transformational leadership on employee performance with quality work life as a mediating variable. This research was conducted on employees who handle the procurement of goods/services within the Probolinggo City Government. The population in this research as a whole is employees from departments, agencies, divisions, sub-districts, sub-districts, schools, hospitals and health centers within the Probolinggo City Government, totaling 190 people. The sample population was 100 people. Data analysis in order to test the hypothesis in this study used Smart PLS 3.2.9. Based on the results of the data analysis that has been carried out, it can be concluded as follows: good competence is able to encourage an increase in the quality of work life, good transformational leadership is able to encourage an increase in the quality of work life, good competence is able to encourage an increase in employee performance, good transformational leadership is able to encouraging increased employee performance, good quality of work life is able to encourage increased employee performance, good quality of work life is able to mediate the influence of competence on employee performance.